Evaluating the Kampus Mengajar Program for Home Economics and Fashion Education Students - Sri Wahyuni; Muh Fakhrihun Na'am; Sri Endah Wahyuningsih (Universitas Negeri Semarang, 2025)
The Merdeka Belajar–Kampus Merdeka (MBKM) policy represents a key government initiative in Indonesian higher education. Universitas Negeri Semarang, as one of the universities supporting MBKM, has undertaken various preparation and implementation efforts. Within this framework, the Home Economics and Fashion Education study programs actively participate in the Kampus Mengajar (Teaching Campus) program—one of the eight flagship MBKM programs. This study focuses on the implementation of Kampus Mengajar in these two programs, with particular attention to activities in target schools and the mentoring and guidance provided by supervisors and mentor teachers. The objectives are: (1) to analyze the implementation of Kampus Mengajar in the field, including mentoring and guidance activities that contribute to program success, and (2) to assess program achievement for Home Economics and Fashion Education students through case studies involving observation, monitoring, and interviews. This qualitative research employed triangulation-based data analysis to ensure validity. The findings indicate that the program has been implemented satisfactorily but has not yet achieved full effectiveness. Key challenges include limited socialization in target schools, inadequate facilities and infrastructure, lengthy adaptation periods, low literacy and numeracy skills among school students, and limited use of interactive learning media. Evaluation results, based on distributed questionnaires, show that while the program operates well, its effectiveness remains partial. Mentoring and guidance processes are conditional and flexible but structured to meet students’ needs. These findings provide evidence-based insights for improving the future implementation of Kampus Mengajar in higher education contexts.